WAYS TO CORRECT CALCIUM DEFFICIT AMONG CHILDREN - N.I. Taibulatov; L.S. Namazova (Педиатрическая фармакология)
The article is dedicated to the urgent issue of the pediatrics — calcium deficit among children. The authors provide modern data on the scheme of the normal calcium exchange in the human body. They also review the main diseases related to the disorders of the pho sphorocalcic metabolism, requiring prompt prevention and treatment by calcium based medications. The researchers stress the diseases of the musculoskeletal system, as insufficient calcium, phosphorus and vitamins supply of the child's body chiefly effects the state of the skeletal and muscular tissue. They give recommendations how to use the vitamin and mineral complex to correct calcium deficit.Key words: calcium deficit, diseases of the musculoskeletal system, vitamin and mineral complex, children.